2023
DOI: 10.1088/2053-1591/acf09f
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanical properties of 2219 aluminum alloy bobbin tool friction stir welding

Xitong Li,
Tiancheng An,
Jinlong Lan
et al.

Abstract: The Bobbin tool friction stir welding (BT-FSW) process experiment was performed on 2219 aluminum alloy with different butt clearances and misalignments. The maximum allowable clearance and misalignment amount for BT-FSW were obtained, and the weld formation, mechanical properties and microstructure under different parameters were compared and analysed. The results show that the face and back sides of the weld joint surface are perfect and there are no defect inside with the butt clearance under 2mm and the mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Elemental analysis of the precipitate phase using EDS revealed that aluminum (Al) accounts for 59.22%, while copper (Cu) accounts for 40.78%. It is speculated that this is Al2Cu, which aligns with the results obtained by other scholars [19][20][21][22][23]. The TMAZ, as shown in Figure 4b,e at different magnifications, undergoes stirring and welding thermal cycles.…”
Section: Analysis Of Microscopic Properties and Partition Of 2219 Alu...supporting
confidence: 90%
“…Elemental analysis of the precipitate phase using EDS revealed that aluminum (Al) accounts for 59.22%, while copper (Cu) accounts for 40.78%. It is speculated that this is Al2Cu, which aligns with the results obtained by other scholars [19][20][21][22][23]. The TMAZ, as shown in Figure 4b,e at different magnifications, undergoes stirring and welding thermal cycles.…”
Section: Analysis Of Microscopic Properties and Partition Of 2219 Alu...supporting
confidence: 90%
“…This is caused by the occurrence of intermetallic Al 3 Sc in the WN as well as inexplicable Sc elements in the matrix of aluminium. Due to differences in microstructure, the TMAZ and HAZ displayed lesser hardness [39][40][41].…”
Section: Microhardnessmentioning
confidence: 99%